(3JRjjf GdeLGdS HPcQ GdJMa GdfaGFS hecfhf MSGf GdYQGFSs - (3CejQ GdeDefjf GdegOj dOjf Gddg CMeO Hf jMji Hf GdeQJVis; (3YeQ Hf CMeO Hf Ydj GdTeGY GdMdHj GdTGaYj, CHh MaU, Rjf GdOjf,J (B936 (3g` s ((3CMeO Hf eMeO Hf MSf GdCchY s)
(3ChdgG (B:s
(3bWY GdNhV GdfaSGfjI hYOe GdJYdb HGdHQjI, hGdJSdje aj LejY GdMGdGJ s
(3BNQgG (B:s
(3Je GdcJGH hcGf (B[(3GdaQGZ(B] (3ef JCdja BNQ TghQ SfI KdGK hKeGfeGFI aj MejeI Hfj GdefJGH s
(3Vef eLehY s
(3hgj NGJeI jhGbjJ GdSjQ aj TQM cJGH GdLhGgQ hGdOQQ ef SjQI SjO GdHTQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs